1990
DOI: 10.1007/bf00030059
|View full text |Cite
|
Sign up to set email alerts
|

Chloride binding proteins: mechanistic implications for the oxygen-evolving complex of Photosystem II

Abstract: Chloride plays a key role in activating the photosynethetic oxygen-evolving complex (OEC) of Photosystem II, but the OEC is only one of many enzymes affected by this anion. Some of the mechanistic features of Cl(-) involvement in water-splitting resemble those of other proteins whose structure and chemistry are known in detail. An overview of the similarities and differences between these Cl(-)-binding systems is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 219 publications
3
45
0
2
Order By: Relevance
“…Manganese was recognized as an essential element for oxygenic photosynthesis more than 60 years ago (31). Subsequently, Ca 2ϩ and Cl Ϫ were also identified as required components (32)(33)(34)(35). Depletion of these components from the growth medium or their removal from photosynthetic membranes (thylakoids) results in loss of the ability to evolve oxygen, although the light reactions themselves are not impaired.…”
Section: The Photosynthetic Water Oxidation Enzymementioning
confidence: 99%
“…Manganese was recognized as an essential element for oxygenic photosynthesis more than 60 years ago (31). Subsequently, Ca 2ϩ and Cl Ϫ were also identified as required components (32)(33)(34)(35). Depletion of these components from the growth medium or their removal from photosynthetic membranes (thylakoids) results in loss of the ability to evolve oxygen, although the light reactions themselves are not impaired.…”
Section: The Photosynthetic Water Oxidation Enzymementioning
confidence: 99%
“…Chloride is an essential co-factor for oxygen evolution (reviewed in Homann 1987, Coleman 1990, Yocum 1992, and there have been several suggestions that C1-might be a ligand to the Mn cluster. Analysis of the EXAFS spectra of PS II samples provided no obvious evidence of C1-in the immediate coordination environment of the Mn (Yachandra et al 1986b, 1987, McDermott et al 1988, Penner-Hahn et al 1990).…”
Section: Chloride and Bromidementioning
confidence: 99%
“…A more comprehensive survey of the literature in the field of oxygen evolution is provided in the reviews by Babcock (1987), Debus (1992) and Rutherford et al (1992). The EPR properties of the OEC are reviewed by Brudvig (1990) and by V/inngfird et al (1992), the role of Ca and chloride in the OEC by Yocum (1991Yocum ( , 1992 and chloride by Homarm (1987) and Coleman (1990), and the mechanistic aspects of photosynthetic water oxidation by Renger (1987a).…”
Section: Introductionmentioning
confidence: 99%
“…This side of PSII is located within the closed lumenal surface of thylakoid membranes, and composed of three extrinsic polypeptides of approximate molecular masses 17, 23 and 33 kDa. At least three inorganic cofactors, CI-, Ca 2+ and Mn 2+, are reported to be associated with these polypeptides (see reviews by [5,6,7,8]). By using detergent-derived PSII membrane fractions, in which the donor side is exposed to outer environment [9], it was shown that Pb z+ competitively inhibited Ca 2+ and C1-binding [10], and Zn 2+ non-competitively inhibited Ca 2+ and Mn 2+ binding [11] at native sites on water oxidase.…”
Section: Introductionmentioning
confidence: 99%